Low cycle fatigue analysis of marine structures - Ng, Wen Hao. (2013)
Fatigue fracture has affected the aircraft industry largely due to the high cyclic loadings of the airplane. However, in recent years, marine structures are found to fail at loading cycles lower than the design life. This brings to the attention of researchers about low cycle fatigue which occur at cycles lesser than 104 cycles.